FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) PROVINSI BALI MENERIMA ASPIRASI RAKYAT DI DALAM MEWUJUDKAN PEMERINTAHAN YANG DEMOKRATIS - Pradnyana, Agus; Suantra, I Nengah; Suarbha, I Wayan (Kertha Negara : Journal Ilmu Hukum, 2013)
The functions of the Local House of Representative of the Province of Bali (DPRD Bali) are the regulation maker and supervising function. In order to establish democratic government the people aspiration has to be seriously considered. The issues in this article are :1. to examine the legal basis of the authority of DPRD Bali to receive the people aspirations, 2. to examine the function of the function of the deliberation of people aspiration through DPRD Bali. purpose of this study was to assess the function of the Regional Representatives Council (DPRD) of Bali in realizing the aspirations of the people in order to establish. The Conclusion are : 1. DPRD Bali is an absorber of aspiration of the community as stated in the mandate of Article 300 letters (J) of Law No. 27 of 2009 and the Rules of Procedure of the Provincial Parliament of Bali No. 9 of 2010, 2. Through DPRD’s role as an absorber of aspiration of the community, people are expected to participate by providing feedback or complaints in the area so as to promote the establishment of a democratic government.
Keywords: Local House of Representative, People Aspiration, Democratic Government